Vitamin D level among elite wrestlers in Uzbekistan - Umarov, J.; Kerimov, F.; Toychiev, A.; Osipova, S. (International Journal of Wrestling Science, 2018)
Purpose. The purpose of the study is to determine vitamin D (VD) levels and acute upper respiratory tract infections (URI) morbidity among elite wrestlers in Uzbekistan as well as possible association with overtraining syndrome (OS). Methods. Study participants included 40 elite wrestlers and 60 control individuals. Serum levels of 25(OH) VD and TNF-á, IFN-ã and IL-4 were detected by ELISA technique. Frequency of URI was detected as well as parasitic infections. OS was diagnosed on the basis of typical symptoms and decreased performance. Results. Predominance of VD insufficiency was found in both groups of elite athletes and in the control individuals. Prevalence of VD deficiency/insufficiency depends on the season, but in every season the highest values were observed among athletes. The highest level of TNF-á and the lowest of IFN-ã were observed in athletes with VD deficiency. Changes in the level of IL-4 were less expressed. Frequency of episodes of URI depends on VD level and the most number was detected in wrestlers with VD deficiency in winter-spring. OS was diagnosed in wrestlers free of infections, including parasitic ones, but with VD deficiency. Conclusion. VD deficiency/insufficiency is widely spread both in elite wrestlers and population in Uzbekistan. Monitoring of VD level in elite athletes with subsequent correction is necessary. VD deficiency/insufficiency in athletes correlates with high morbidity with URI and could be associated with OS.